2013
DOI: 10.3945/ajcn.113.058727
|View full text |Cite
|
Sign up to set email alerts
|

Plasma S-adenosylhomocysteine is associated with the risk of cardiovascular events in patients undergoing coronary angiography: a cohort study

Abstract: Higher concentrations of plasma SAH are independently associated with an increased risk of cardiovascular events among patients undergoing coronary angiography. This trial was registered at www.chictr.org as ChiCTR-RNRC-08000270.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…[20][21][22][23] EGCADC consisted of patients aged from 40 to 80 years old recruited from GCADC and outpatients from Guangdong General Hospital following the same inclusion and exclusion criteria, ascertainment of CAD, questionnaires and study protocol. A total of 2523 CAD patients were included in the EGCADC (1513 from GCADC and another 1010 from Guangdong General Hospital).…”
Section: Study Subjectsmentioning
confidence: 99%
“…[20][21][22][23] EGCADC consisted of patients aged from 40 to 80 years old recruited from GCADC and outpatients from Guangdong General Hospital following the same inclusion and exclusion criteria, ascertainment of CAD, questionnaires and study protocol. A total of 2523 CAD patients were included in the EGCADC (1513 from GCADC and another 1010 from Guangdong General Hospital).…”
Section: Study Subjectsmentioning
confidence: 99%
“…Methylation is essential for critical cell processes, including gene expression and protein function (45,46). SAH, which is one of the most potent in vivo modulators of AdoMet-dependent methylation reactions, is an important regulator of cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…SAH, which accumulates in the setting of hyperhomocysteinemia, has gained attention as an intracellular metabolite that may be responsible for the deleterious actions on the vasculature attributed previously to excess Hcy (46). Our studies are focused on the effects of SAH as a hypomethylating agent that alters endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one recent cohort study prospectively evaluated the association between plasma SAH levels and CVD risk in patients undergoing coronary angiography (Xiao et al, 2013). The study found that higher plasma SAH concentrations were significantly associated with an increased risk of cardiovascular events, including fatal CVD, nonfatal myocardial infarction, and stroke.…”
Section: Sah and Cardiovascular Diseasementioning
confidence: 95%
“…Several previous cross-sectional and case-control studies have indicated that plasma SAH may be a better indicator of cardiovascular disease than homocysteine (Kerins et al, 2001;Valli et al, 2008;Wagner and Koury, 2007). A recent prospective cohort study also found that higher plasma SAH levels were significantly associated with an increased risk of cardiovascular events and were a better predictor of cardiovascular risk than homocysteine in coronary angiographic patients (Xiao et al, 2013). Furthermore, Liu et al (2008) showed that plasma SAH levels were a more sensitive biomarker of atherosclerosis than homocysteine and were associated with DNA hypomethylation in HHcy mice.…”
Section: Introductionmentioning
confidence: 92%